P1-S6.18 Characteristics of men who seek rescreening for STIs after once using the http://www.iwantthekit.org screening program. (10th July 2011) - Hsieh, Y H; Barnes, M; Jett-Goheen, M; Quinn, N; Agreda, P; Whittle, P; Hogan, T; Gaydos, C
Abstract : Background: The iwantthekit (IWTK) Internet screening program offered an opportunity to study characteristics of men who seek rescreening, as well as determine reported infected status at the previous screening. Methods: We determined characteristics of male repeat users from questionnaires. Predictors of repeat users were identified in a matched case-control study by conditional logistic regression analysis. A case was defined as reporting ever having used IWTK before. A control was a user who reported never using the program before. Two controls were systematically sampled for each case by matching the date of use IWTK of the case within 3 months. Results: During 2007–2010, 115 (14%) of 852 men who used IWTK for STI testing, indicated that they had used IWTK previously. Among them, 43% used it >2 times. Mean age was 25.8 yr ±8.5 yr, and 90% were currently sexually active. 17% reported having sex with a male; 35% had >5 partners in the past yr; 58% had new partners in last 3 months; 49% currently were having sex >1 person. 63% had been treated for an STI: chlamydia (CT)(74%), trichomonas (TV)(42%) and gonorrhoea (GC)(23%); 6 reported being treated for HIV. By matching time of enrolment, 230 controls were selected. In the multivariate analysis, repeat IWTK users were more likely to be <30 years (OR=2.04, 95% CI 1.04 to 4.02), have health insurance (OR=2.01, 95% CI 1.10 to 3.69), reported ever being tested for an STI (OR=2.01, 95% CI 1.02 to 3.97), ever been treated for an STI (OR=2.20, 95% CI 1.14 to 4.23), particularly TV (OR=5.16, 95% CI 1.80 to 14.81), and less likely to have penile discharge currently (OR=0.24, 95% CI 0.08 to 0.76). Of male repeaters, 80.9% reported previous test results from IWTK as negative and 22/115 (19.1%) reported previous result positive–11 had CT, 4 had GC, 8 had TV; 2 of these were mixed infections. At present test, 24 tested positive–19 had CT, 3 had GC, 5 had TV; 3 were mixed infections. Reported CT positivity in last test was associated with current CT test positivity (p<0.05). Conclusions: The Internet screening program IWTK attracted a number of previous male users of IWTK, who practiced high-risk sexual behaviours, to use the program for repeat STI testing. IWTK provided an alternate approach for rescreening previously infected men as well as men reporting high-risk behaviours.